Changes and predictors of premarital sex intercourse among never-married women (15–24 years) in Nigeria: A multilevel approach - Joseph Ayodeji Kupoluyi (PLoS ONE, 2025)
Introduction Premarital sexual intercourse (PSI) predisposes never-married women to unwanted pregnancy, abortion, sexually transmitted infections, HIV/AIDS, and high rates of school dropout. This study examines changes and predictors of PSI among never-married women (15–24) in Nigeria. Methods The study used a 15-year duration of three wave’s pooled individual recode (IR) dataset of the Nigeria Demographic and Health Surveys (NDHS) of 2008, 2013, and 2018. A weighted sample size of 23,446 never-married young women was analysed using frequency tables, charts, and multilevel binary logistic regression. Results The prevalence of PSI among never-married women (15–24) over the 15-year duration of 3 waves of NDHS datasets was 31.3% [95%CI: 30.3, 32.3] in Nigeria. Prevalence of PSI steadily decreased from 36.8% in 2008 to 31.7% in 2013 and 26.6% in 2018. A 5-year percentage change between 2008 and 2013 showed that PSI declined by 13.2%, 16.2% between 2013 and 2018, and 27.7% over 10 years (2008–2018). Never-married women aged 20–24 had higher odds (OR= 7.8, 95%CI [6.9, 8.8], p < 0.001) of engaging in PSI than those aged 15–19. The community’s knowledge of modern methods, literacy level, socio-economic status, education, religion, region of residence, employment status, and exposure to mass media were strongly associated with PSI. The intra-class correlation value of 10.1% indicates that contextual factors significantly explained the variations in PSI between clusters. The proportional change in variance of 41.3% explained the variability in the odds of PSI explained by each model with more terms. Conclusion This study established a steady decrease in the prevalence of PSI among never-married women (15–24) over the 15-year duration of 3 waves of NDHS datasets (2008, 2013, and 2018). Thus, we conclude that concerted efforts are required to empower young women to contribute to a further reduction in PSI to improve the general national health status of women and to ensure progress towards achieving a reduction in early pregnancies among unmarried women in Nigeria.